Role of Hepatocyte Growth Factor in the Immunomodulation Potential of Amniotic Fluid Stem Cells. (14th April 2015) - Maraldi, Tullia; Beretti, Francesca; Guida, Marianna; Zavatti, Manuela; De Pol, Anto
Abstract : New information about the secretome pattern is reported in this paper. Human amniotic fluid stem cells (hAFSCs) possess immunomodulatory properties involving hepatocyte growth factor production. hAFSCs could be used in immunotherapies and might be able to avoid allogenic rejection. Abstract: : Human amniotic fluid stem cells (hAFSCs) may be useful for regenerative medicine because of their potential to differentiate into all three germ layers and to modulate immune response with different types of secretion molecules. This last issue has not been completely elucidated. The aim of this study was to investigate the secretome profile of the hAFSC, focusing on the role of hepatocyte growth factor (HGF) in immunoregulation through short and long cocultures with human peripheral blood mononuclear cells. We found that HGF produced by hAFSCs exerts a cytoprotective role, inducing an increase in caspase-dependent apoptosis in human immune cells. This study provides evidence supporting the hypothesis that amniotic fluid is an ideal source of stem cells for expansion and banking properties for therapeutic use. hAFSCs not only are less immunogenic but also can secrete immunoregulatory factors that may be useful in autoimmune diseases or allogenic implants. Significance: New information about the secretome pattern is reported in this paper. Human amniotic fluid stem cells (hAFSCs) possess immunomodulatory properties involving hepatocyte growth factor production. hAFSCs could be used in immunotherapies and might be able to avoid allogenic rejection.